2020
DOI: 10.3390/s20154333
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Learning Control for a Soft Exoskeleton with Hip and Knee Joint Assistance

Abstract: Walking on different terrains leads to different biomechanics, which motivates the development of exoskeletons for assisting on walking according to the type of a terrain. The design of a lightweight soft exoskeleton that simultaneously assists multiple joints in the lower limb is presented in this paper. It is used to assist both hip and knee joints in a single system, the assistance force is directly applied to the hip joint flexion and the knee joint extension, while indirectly to the hip extension also. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In order to evaluate whether the exoskeleton interfered with the subjects' movement in the following mode, such as walking between the workbenches of the assembly line. The wearable metabolic system (K5, COSMED, Italy) was adopted to measure the concentration and volume of the exhaled pulmonary gas, which are mainly carbon dioxide and oxygen (Chen et al, 2020).…”
Section: Metabolic Cost Measurementmentioning
confidence: 99%
“…In order to evaluate whether the exoskeleton interfered with the subjects' movement in the following mode, such as walking between the workbenches of the assembly line. The wearable metabolic system (K5, COSMED, Italy) was adopted to measure the concentration and volume of the exhaled pulmonary gas, which are mainly carbon dioxide and oxygen (Chen et al, 2020).…”
Section: Metabolic Cost Measurementmentioning
confidence: 99%
“…The relatively easy control strategy is to provide a consistent force (about 50-100 N), simultaneously the executive force time starts from the maximum rotation angle of the hip joint in the positive direction to the end of the maximum rotation angle in the negative direction, which strategy is relatively simple and only needs to detect the changing conditions to provide the force. In some papers, many complex functions [29] are used as the function of the force, some of which are even difficult to express with mathematical formulas.…”
Section: Assistance Forcementioning
confidence: 99%
“…The joints of human body lower limbs will generate torque during walking, which can be referred to as the desired force. Our team used the Vicon (a device for capturing motion) to capture the motion state of the human body's lower limbs, and utilizes the human body model in Anybody (a kind of human motion simulation software, Denmark) to calculate the angle and torque of each lower limb joint in real time [29]. The biological torque of hip joint when walking on the ground is shown in Figure 4, where it can be discovered that in the first 1/2 cycle, which was a suitable assisting time, the biological torque of hip joint was similar to a sine curve.…”
Section: Assistance Forcementioning
confidence: 99%
See 1 more Smart Citation
“…It corrects the control signal according to the deviation between the output signal and the desired target, so as to improve the tracking performance of the system [37]. Iterative learning control is significant for nonlinear, strong coupling, difficult to model and repetitive motion of the controlled system [38], and it has been widely used in robot control, traffic flow control, industrial process, biomedical engineering and many other practical problems [39][40][41][42][43][44]. These practical problems have similar characteristics with the open container motion model with sloshing constraints, but the relevant research work is seldom reported at present.…”
Section: Introductionmentioning
confidence: 99%